Crystal structure of peroxiredoxin 3 from Vibrio vulnificus and its implications for scavenging peroxides and nitric oxide. (2018) - Ahn, Jinsook; Jang, Kyung Ku; Jo, Inseong; Nurhasni, Hasan; Lim, Jong Gyu; Yoo, Jin-Wook; Choia, Sang Ho; Ha, Nam-Chul
No abstract available